Breakfast Habits and Weight Status of Adolescents Aged 17-19 Years Living In Sandilipay Medical Officer of Health Area, Jaffna District - Sivakaran, M.; Arasaratnam, V.; Surenthirakumaran, R. (Open University of Sri Lanka, 2024)
Adolescence period is characterized by rapid growth and maturation, making nutritional status during this stage vital for overall health. Dietary patterns established during the adolescence period have an impact on health status in later life. Breakfast, being the first and most important meal of the day, plays a significant role in school performance and overall well-being. Despite its importance, skipping breakfast is a common practice among the adolescents. The study aimed at assessing the breakfast habits, weight status and factors associated with irregular breakfast consumption among adolescents in the Sandilipay Medical Officer of Health (MOH) area of Jaffna district. A multistage stratified cluster sampling method was employed using an interviewer- administrated questionnaire with a 24-hour dietary recall and a one-week food diary to gather socio-demographic information and dietary habits. A total of 92 adolescents, aged 17 to 19 years, were interviewed through household visits in three Grama Niladhari divisions. Weight and height were measured and Body Mass Index (BMI) was calculated. Ethics Review Committee, Faculty of Medicine, University of Jaffna gave the ethical approval. Among the 92 participants, the majority were female (n=54, 58.7%). The mean ages for male and female adolescents were 18.37 (±0.8) and 18.07 (±0.8) years, respectively. About 31.5% (n=29) of the adolescents skipped breakfast on two or more days during the study week. Pittu, prepared with wheat flour, was the most frequently consumed breakfast item, followed by string hoppers, bakery products, rotti, dosa, idli, pulses, milk rice, samaposa, and biscuits. Key factors that lead to the avoidance of the breakfast were, not getting ready early to go to school, fasting based on religious reasons, disliking the food prepared or bought for breakfast and delay in preparing or buying the breakfast. Among the adolescents, 35.9% (n=33) were underweight. Notably, over half of these underweight adolescents (54.5%, n=18) had skipped breakfast on two or more days. This finding highlights the urgent need for targeted interventions to promote regular breakfast consumption, given its critical role in maintaining overall health and nutritional status in Sandilipay MOH area.
Keywords: Adolescents; Breakfast; Jaffna; Underweight; Nutritional status